Knowledge and Perception of "Do Not Resuscitate" (DNR) Among Health Care Providers in Pediatric Emergency Departments: A Cross-Sectional Study in a Resource-Limited Country - Syed Muhammad Umair Hamid; Irfan Habib (Pakistan Journal of Medical & Health Sciences, 2024)
Background: A busy Pediatric Emergency Department (PED) receives hundreds of critical patients daily. Providing maximum treatment to stabilize the patient is the primary goal of every PED. Many patients require advanced support like cardiopulmonary resuscitation (CPR), ventilators, or inotropes but providing these advanced supports to every sick child is difficult, particularly in a resource-limited country, prompting health care workers to make “do not resuscitate” (DNR) decisions. Aim: To determine the basic knowledge and perception of DNR among health care providers working in PED of tertiary care hospitals in a resource-limited country. Methods: A cross-sectional study was conducted in three public sectors PED in Karachi. Pakistan. The study was determine the basic knowledge and perception of DNR among health care providers working in PED of tertiary care hospitals in a resource- limited country. Data was collected from doctors and nurses working in these PED through a questionnaire consisting of ten questions to meet the objectives of the study. Results: There was a total of 59 providers who participated in the study, with 36(61%) being nurses and 23(39%) being physicians. Notably, 46(78%) had been involved in DNR decision-making during their careers, underscoring the relevance and importance of this research. The study revealed that 50(85%) of the participants knew the term DNR, but their knowledge of sub- categories such as full code (47.5%), comfort care (40%), and DNR with additional limitation (30%) was found to be deficient. Moreover, 52.5% believed DNR means not doing CPR but continuing pharmacological support, while 35.6% thought it means not doing CPR and discontinuing pharmacological support. The participants’ perceptions regarding authority in decision making showed that 63% thought that physicians have the right to decide DNR, while 59% believed it should be parents, 20% relatives, 18% nurses, and 17% the ethical committee. 75% of the participants reported being taught about DNR during their training. Conclusion: The majority of the healthcare providers are familiar with the term DNR, and they have also been part of decision making. However, complete knowledge about the DNR policy is lacking among the participants. A sustainable educational program on clinical and ethical issues about DNR can help to improve practices on this sensitive matter. Keywords: CPR (Cardiopulmonary-resuscitation), DNR (do-not-resuscitate), Ethics